Hibernate Recipes: A Problem-Solution Approach - Guruzu, Srinivas (Apress, 2012)
Would I do it again? Writing a book, I mean. Of course, Yes! However, anyone who believes a book project is a simple effort does not have any idea what goes into it. It takes a lot of commitment, focus, and support from family and friends. Josh Long, thank you, thank you, thank you very much for introducing me to Apress; for believing in me and guiding me through everything that a new author like me needed to know. Gary Mak, thank you, for trusting me and letting me be a co-author for this book. Thank you, Apress and Steve Anglin for giving me the opportunity to write this book and trusting Josh Long’s instincts. Tom Welsh, Sumit Pal, and Dionysios G. Synodinos, thank you, for reviewing and providing excellent suggestions. Being a first time author, the suggestions provided were of immense help in developing the book. Anita Castro answered the book and non-book related questions very patiently. Tiffany Taylor helped with grammer, spelling and consistency throughout the book. I am very grateful for support and help provided by the Apress team. To my lovely wife, Usha, without whom I would not have been able to complete this book.